Interlanguage Phenomena in Learning Arabic - Kurniati, Depi; Marwa, Atikah; Desrani, Ayu (Proceeding of International Conference on Islamic Education (ICIED), 2019)
Arabic is a foreign language in Indonesia that is obtained outside the actual situation. So the learning process will experience various obstacles. This study aimed to find out about the processes that occur in interlanguage and the factors that caused the interlanguage. Interlanguage error data of students in this study were obtained from observations, interviews and essays from students in MTs Muqimusunnah Palembang from grades 7-8 randomly selected. Then the data was analyzed qualitatively. This study showed that the interlanguage process in learning Arabic wasinterlingual transfer, overgeneralization, and code-switching. Of the three processes, the process or strategy most widely used by students wereinterlingual transfer, which was 48 times, 39 times of overgeneralizations and 5 times of code-switching. 4 factors were causing this interlanguage, they were: 1. absence of rules, 2. students lack mastering Arabic, 3. Environment, 4. the absence of improvement directly.